A three-dimensional numerical study of hydraulic fracturing with degradable diverting materials via CZM-based FEM. (1st October 2020) - Wang, Daobing; Dong, Yongcun; Sun, Dongliang; Yu, Bo
Highlights: A comprehensive workflow to model hydraulic fracturing with diverters in naturally fractured formations. A fully coupled finite element model with consideration of seepage flow, fracture flow, and rock deformation with adaptive insertion of cohesive elements as crosscutting natural fractures. Spring elements are used to model the temporary plugging behaviour. Abstract: Both microseismic interpretation and post-frac production analysis have confirmed that initial hydrocarbon production and ultimate recovery in reservoirs are mainly associated with the degree of fracture complexity. Hydraulic fracturing with degradable diverting materials is an effective technology for enhancing fracture complexity. However, the physics behind the effectiveness of this technology is not fully understood at present. In this paper, we first present a comprehensive workflow to model hydraulic fracture by accounting for interactions with numerous crosscutting natural fracture or joint sets, as well as the effect of temporary plugging in opened fractures. This model is a fully coupled seepage flow in porous media, fluid flow in fractures, and rock deformation finite element model with adaptive insertion of cohesive elements as crosscutting natural fracture or joint sets. In addition, spring elements are used to model the temporary plugging behavior that can be automatically activated once the diverters are injected into the opened fractures. Numerical simulations that correspond to the orthogonal and non-orthogonal approach angles have been implemented for the model. Our analysis shows that key factors such as the tensile and shear strength of natural fracture or joint sets, horizontal stress anisotropy, and the position of temporary plugging can play a significant role in the enhancement of fracture complexity and the diversion into natural fracture or joint sets. Adding degradable diverting materials has a particularly noticeable effect on enhancing fracture complexity and helps overcome cohesive resistance at the intersections. This investigation provides new insight into the formation mechanism of fracture networks in naturally fractured formations.